The Attractiveness of TikTok Live Shopping to User Emotional Satisfaction - Sunuantari, Manik; Mandjusri, Alma; Gunawan, Imsar; Farhan, Raihan Muhammad (UPT Publikasi Ilmiah UNISBA, 2023)
The aftermath of the Covid-19 Pandemic had an impact on the physical and mental health. Even for workers, it causes anxiety due to job loss. The background of this research is the phenomenon of a pandemic that causes excessive public pressure. The emergence of Tik Tok Live Shopping in 2022 provides an alternative to building people’s mental health during the Covid-19 pandemic. TikTok Live Shopping is one of the social media that offers real-time entertainment functions. This study aims to determine the effect of the attractiveness of TikTok Live Shopping on User Emotional Satisfaction. The theory used is emotional gratification as a derivative of the gut and gratification theory. Attractiveness is measured on three dimensions: source credibility, content creator, and message content. This study used an explanatory method, purposive sampling technique, and multiple regression analysis as data analysis. The results of the study show that there is an influence between the attractiveness of TikTok Live Shopping on User Emotional Satisfaction. User satisfaction is indicated by emotional involvement. Through TikTok Live Shopping, users can feel the sensation and have a direct experience. This, the research hypothesis is accepted, the use of TikTok Live Shopping contributes to providing emotional satisfaction to its users.